2019
DOI: 10.1002/nbm.4065
|View full text |Cite
|
Sign up to set email alerts
|

In vivo 1H MRS of human gallbladder bile in understanding the pathophysiology of primary sclerosing cholangitis (PSC): Immune‐mediated disease versus bile acid‐induced injury

Abstract: Primary sclerosing cholangitis (PSC) has been considered to be either an "autoimmune disease" or a "bile acid-induced injury." In vitro MRS studies on PSC patients have limitations due to the contamination of bile with contrast agent (commonly administered during endoscopic retrograde cholangiopancreatography) and/or the use of patient cohorts with other diseases as controls. The objective of this study was to quantify biliary metabolites using in vivo 1 H MRS and gain insight into the pathogenesis of PSC. Bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 45 publications
(105 reference statements)
0
21
1
Order By: Relevance
“…Lower concentrations of bile components in patients with PSC have already been reported. 10 The authors of that study suggested that the reduction in bile acid secretion could indicate accumulation of bile acids in hepatocytes. The results reported in our study support previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower concentrations of bile components in patients with PSC have already been reported. 10 The authors of that study suggested that the reduction in bile acid secretion could indicate accumulation of bile acids in hepatocytes. The results reported in our study support previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…More recent MRS studies of healthy subjects and patients with PSC were performed at 3T. 9,10 Ultrahigh field of 7T has promising advantages for MRS, such as high spectral resolution and higher signal-tonoise ratio (SNR), which could help better resolve bile components and acquire spectra faster.…”
mentioning
confidence: 99%
“…The study in humans by Prescot et al 8 was performed at 1.5 T, which limited the number of detectable metabolites. The two other 1 H‐MRS studies in human gallbladder, both by Mohajeri et al, 9,10 show excellent 1D and 2D spectra acquired on a 3 T MR scanner. A 1 H‐MRS study performed at 4.7 T in the gallbladder of cynomolgus monkeys also demonstrated good 1 H‐spectra, 11 and intra‐ and inter‐individual variability was determined.…”
Section: Introductionmentioning
confidence: 86%
“…Other techniques such as extended 2D-COSY scans provide extended information on the bile composition, eg differentiation of phosphatidylcholine from its hydrolysis products. 9,10 However, this benefit comes at prolonged measurement times of approximately 50 min, which might be challenging for some patients due to the prone position.…”
Section: Quantificationmentioning
confidence: 99%
See 1 more Smart Citation